Advanced Non-Small Cell Lung Cancer with Activating Epidermal Growth Factor Receptor Mutation: First Line Treatment and Beyond - Rocco, Danilo; Battiloro, Ciro; Gravara, Luigi D.; Gridelli, Cesare (Reviews on Recent Clinical Trials, 2019)
Background: Lung cancer is the leading cause of cancer mortality, being responsible for more than 1.6 million deaths each year worldwide and non-small-cell lung cancer (NSCLC) accounts for approximately 85% of lung cancers; moreover, 10 to 15% of all NSCLCs harbor EGFR (epidermal growth factor receptor) activating mutations, being suitable for EGFR-Tyrosine Kinase Inhibitors (TKI) molecular targeted therapy. However, EGFR+ NSCLCs gain acquired resistance to these agents, representing one of the key challenges for modern precision oncology. Objective: Therefore, this paper aims to provide an extensive state of the art review, alongside with hints about future perspectives. Conclusion: To date, in the light of the data from the FLAURA study, osimertinib represents the best first-line option in NSCLC patients with EGFR activating mutations; EGFR-TKI plus chemotherapy combination therapies, even though interesting, must still be considered investigational.
Keywords: Combination therapy